Abordagem dos aspectos psicológicos da mulher infértil :um estudo quali-quantitativo - Moreira, Simone da Nóbrega Tomáz (2004)
Purpose: assess the frequency of stress and anxiety levels in infertile women, correlate these aspects with risk factors and qualitatively analyze feelings resultant from the inability to conceive, in order to obtain data for specific psychological guidance. Methods: the case-control study included a total of 302 women, 152 being infertile (case group: 30.3 ± 5.4 years), and 150 non-fertile (control group: 25.7 ± 7.9 years). The quantitative approach involved the application of Lipp s Stress Symptoms Inventory (LSSI) and State-Trait Anxiety Inventory (STAI), whereas the qualitative approach consisted of a semi-structured interview. Response variables considered were: stress frequency and anxiety scores (State and Trait). Statistical analysis compared frequencies and medians between groups, by means of qui-squared and Mann-Whitney tests, respectively, and constructed logistical regression models to test associations between response variables and risk factors considered. Qualitative data were analyzed descriptively and categorized in order to perform correspondence analysis. The level of significance was 5%. Results: in the study sample, stress frequency was higher in the case group than in the control(61.8 and 36.0%, respectively), however, significant differences were not observed between groups in relation to stress phases and predominant symptomology type. With respect to anxiety, there were no significant differences between case and control groups as to median state scores [39.5 (35.0 46.0) and 41.0 (35.7 47.0 ); respectively) and anxiety trait scores [44.0 (34.0 51.0) and 42.0 (36.0 49.2); respectively). Risk factors significantly associated with greater risk for high anxiety scores in the case group were: primary infertility, unawareness of the causal factor, diagnostic phase investigation, religion, lack of children from other marriages and the fact that the woman was previously married. The qualitative approach demonstrated that infertility provokes emotional responses, such as sadness, anxiety, anger, fear and guilt. Conclusions: it can be concluded that infertile women are more vulnerable to stress; however, they are capable of adapting to stressful events without serious physical or psychological compromising